DIGESTION OF HIGH FIBER DIET IN SHEEP AND GOAT OF JENEPPONTO - Rahardja, D.P.; Lestari, V.S.; Hatta, M. (Diponegoro University, 2010)
Four does (goat, G) and four ewes (sheep, S) of Jeneponto were fed chaffed rice straw hay (3.7%crude protein, 63.5% cell wall constituents, 44.5% acid detergent fiber and 6.2% acid detergent lignin,all based on dry matter). The intakes and digestibility of the diet by G and S were compared. Bothspecies consumed the same level of the diet. G digested dry matter, organic matter, crude protein, crudefiber, and lignin of the diet to a significant higher extent than did by S. The superiority of G over S indigesting the diet was attributable with longer retention time of ruminal fluid and particulate matters inthe rumen and the entire gut, which then resulted in higher proportion of small size particles (<1 mmsieve), higher proportions of propionic, butyric, valeric and isovaleric acid concentrations produced inthe rumen. Additionally for further studies, there were some possibilities of G having a better chewingactivity (duration and intensity), and ability to maintain higher rumen ammonia levels by a greater urearecycle to the rumen, particularly through salivation.